2022
DOI: 10.1101/2022.05.10.491220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transformation of coral communities subjected to an unprecedented heatwave is modulated by local disturbance

Abstract: Corals are imminently threatened by climate change-amplified marine heatwaves. Yet how to conserve reef ecosystems faced with this threat remains unclear, since protected reefs often seem equally or more susceptible to thermal stress as unprotected ones. Here, we disentangle this apparent paradox, revealing that the relationship between reef disturbance and heatwave impacts depends upon the focal scale of biological organization. We document a heatwave of unprecedented duration that culminated in an 89% loss o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 92 publications
0
38
0
Order By: Relevance
“…2). Past work has found that human disturbance can have either negative ( 41 , 49 ) or positive effects ( 80 , 81 ) on coral thermotolerance or survivorship through heatwaves and this has been linked to disturbance-driven changes in the symbiont composition ( 41 , 81 ) or density ( 80 ). Here, we found negative impacts of human disturbance irrespective of symbiont community composition (figs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2). Past work has found that human disturbance can have either negative ( 41 , 49 ) or positive effects ( 80 , 81 ) on coral thermotolerance or survivorship through heatwaves and this has been linked to disturbance-driven changes in the symbiont composition ( 41 , 81 ) or density ( 80 ). Here, we found negative impacts of human disturbance irrespective of symbiont community composition (figs.…”
Section: Resultsmentioning
confidence: 99%
“…Human uses, including wastewater runoff, subsistence fishing, and a large pier, are densely concentrated in this area, while other parts of the atoll experience substantially less human disturbance. The intensity of chronic local human disturbance at each site has previously been quantified, using two spatial data sources: (i) human population densities and (ii) fishing pressure ( 41 , 49 ). First, as a proxy for immediate point-source inputs from villages into the marine environment such as pollution and sewage runoff, a geographic buffer (in ArcGIS) was generated to determine human population size within 2 km of each site.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations